Implementasi Implementasi Peraturan Daerah Kota Sungai Penuh Nomor 2 Tahun 2019 tentang Pemberdayaan Usaha Mikro, Kecil dan Menengah: Pendahuluan - Sri, Sriningsih Hasimi; Budhiartie, Arrie; Fauzani Raharja, Ivan (Fakultas Hukum Universitas Jambi, 2021)
This study aims to find out and analyze how the implementation of Sungai Penuh City Regional Regulation Number 2 of 2019 concerning Empowerment of Micro, Small and Medium Enterprises in Sungai Penuh City; to find out how the authority of Sungai Penuh City Government in efforts to empower Micro, Small and medium enterprises and how the licensing mechanism for Micro, Small and Medium Enterprises. The research method used is empirical juridical and the procedure for sampling is done by purposive sampling. Data collection techniques used through field studies, data obtained directly from the field through respondents. Data analysis in this study used descriptive analysis techniques. The author formulates the formulation of the problem how the authority of the Sungai Penuh City Government in efforts to Empower Micro, Small and Medium Enterprises and how the licensing mechanism for Micro, Small and Medium Enterprises is based on the Sungai Penuh City Regional Regulation. The results of the research that the author obtained were the authority of the Sungai Penuh City Regional Government in the Implementation of Micro, Small and Medium Enterprises. The research method used is empirical juridical and the procedure for sampling is done by purposive sampling. Data collection techniques used through field studies, data obtained directly from the field through respondents. Data analysis in this study used descriptive analysis techniques. The author formulates the formulation of the problem how the authority of the Sungai Penuh City Government in efforts to Empower Micro, Small and Medium Enterprises and how the licensing mechanism for Micro, Small and Medium Enterprises is based on the Sungai Penuh City Regional Regulation. The results of the research that the author obtained were the authority of the Sungai Penuh City Regional Government in the Implementation of Micro, Small and Medium Enterprises Empowerment seen from the criteria and the implementation of empowerment did not run as it should. This is because the business criteria listed in the Ragional Regulation state that the criteria that enter into Small Business are those who have a net income of fifty million rupiah. In Fact, Small Business actors registered in Sungai Penuh City have a net income pf twenty million rupiah. The licensing mechanism has also not run optimally because thre are still many Micro, Small and Medioum Bussines actros who do not register business permits.